Mechanical and Tribological Properties of Plasma Deposited a-C:H:Si:O Films - Lopes, Bruno B.; Rangel, Rita C.C.; Antonio, César A.; Durrant, Steven F.; Cruz, Nilson C.; Rangel, Elidiane C. (IntechOpen, 2012)
None